TEACHER STRATEGIES TOWARDS STUDENTSâ DISRUPTIVE BEHAVIOR IN LEARNING ENGLISH - Shanty, Halim (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2015)
The objective of this paper is to describe about the theory of teachers strategy towards students disruptive behavior. There is no a specific definition for disruptive behavior since the definition differs according to its relevance to the case of each study (Arbuckle & Little, 2004). Nevertheless, many studies identify some types such as self-reported data from schoolteachers which help identify types of the most frequent disruptive behaviors. Ranking which behavior is more frequent differs in Western and Eastern cultures. Selecting effective classroom management strategies can help teachers deal with an important issue that may hinder the learning and teaching process, which is studentsâ disruptive behavior.